Pain Assessment in Emergency Department of Teaching Hospital in Lalitpur - Gauchan, Srijana (Journal of Karnali Academy of Health Sciences, 2019)
Background: Proper pain assessment is directly related to proper pain management.The American pain society (APS) in 1996 instituted “the pain as the 5th vital sign”, in an effort to reduce the burden of underassessment and inadequate pain management. The objective of this study is to find out the practice of pain assessment and to make improvement.Methods: This was an observational study of pain assessment by the medical officer in emergency department (ED).Convenience sampling was done at three different shift in ED. All the data of pain assessment was taken and tabulated and analysed to know the practice of pain assessment. Standard as set at 80%. In first stage data collection was done for one month as per convenience. Following the observed finding, in the second stage intervention was done. After this in third stage re-data collection was done to see the improvement.Results: A total of 503 patients were enrolled in this study. Out of this 53% (n=265) were in first stage and 47% (n=238) in third stage of the study. In first stage of the study there was 7% (n=19) documentation of numerical rating scale (NRS) and PQRST (P-precipitating and palliating factor, Q-quality of pain, R-radiation, S-site of pain, T-timing of pain) was not documented. After intervention in third stage documentation of NRS was done in 70% (n=167) and documentation of PQRST were variable.Conclusions: The study revealed that existing practice of pain assessment in the emergency department is poor but after the intervention there was remarkable improvement in the pain assessment.